2001
DOI: 10.1176/appi.ajp.158.7.1058
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Activity in Autism: Abnormalities in the Cerebral Cortex and Basal Forebrain

Abstract: These neurochemical abnormalities implicate the cholinergic system in developmental disorders such as autism and suggest the potential for intervention based on cholinergic receptor modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
206
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(222 citation statements)
references
References 45 publications
15
206
0
1
Order By: Relevance
“…Conversely, it is of potential importance for the design of nicotinic agents acting on psychiatric or neurologic diseases that hit nAChRs. Various cognitive dysfunctions such as those associated with Alzheimer's disease (45), schizophrenia (46), and autism (10) have been reported to differentially affect diverse subtypes of nicotinic receptors. The phenotypes observed with the ␤2 Ϫ/Ϫ mice are characterized by alterations of behavioral flexibility and adaptive behaviors coupled with unimpaired memory and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, it is of potential importance for the design of nicotinic agents acting on psychiatric or neurologic diseases that hit nAChRs. Various cognitive dysfunctions such as those associated with Alzheimer's disease (45), schizophrenia (46), and autism (10) have been reported to differentially affect diverse subtypes of nicotinic receptors. The phenotypes observed with the ␤2 Ϫ/Ϫ mice are characterized by alterations of behavioral flexibility and adaptive behaviors coupled with unimpaired memory and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, nicotinic antagonists (6,7) and loss of nicotinic acetylcholine receptors (nAChRs) under various pathological conditions impair cognitive performance (8)(9)(10). These pharmacological actions of nicotine are mediated by a variety of nAChR subtypes with different distribution patterns in the brain (11,12).…”
mentioning
confidence: 99%
“…Abnormalities in cortical nicotinic binding have been demonstrated in several neurodevelopmental conditions, including autism (Perry et al, 2001;Martin-Ruiz et al, 2004), epilepsy (Picard et al, 2006), and schizophrenia (Breese et al, 2000;Marutle et al, 2001). In the human brain, nicotinic binding is highest toward the end of gestation (Court et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of BDNF were found in postmortem brain tissue from adults with autism [Perry et al, 2001] and concentrations different from those in controls have been found in peripheral blood of adults and children diagnosed with autism [Connolly et al, 2006;Enstrom et al, 2008;Hashimoto et al, 2006;Miyazaki et al, 2004]. The two studies that have examined BDNF levels in neonatal specimens from individuals later diagnosed with autism have yielded inconsistent results [Nelson et al, 2001[Nelson et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%